Analysis of School Library Management at SD Inpres 1 Tanamodindi - Gagaramusu, Yusdin; Afika, Nurul; Zulnuraini, Zulnuraini; Khairunnisa, Khairunnisa (FKIP - Universitas Riau, 2025)
This research highlights the importance of elementary school libraries as learning resource centers and drivers of early literacy development. Effective management can increase reading interest and support learning. At SD Inpres 1 Tanamodindi, challenges include a shortage of professional librarians, limited new book collections, and manual management. The study analyzes current conditions, challenges, effectiveness, and strategies for improving library management. Using a case study approach, data were gathered through interviews, observations, and documentation involving the principal, library staff, and direct observation. Findings show the library has a clear management structure, adequate facilities, comfortable reading rooms, neatly organized collections, and effective literacy programs, including daily activities and class visits. Obstacles include limited personnel, small collections, manual record-keeping, and space use that interferes with learning. In conclusion, library management at SD Inpres 1 Tanamodindi is well-structured and progressing. Improvement strategies include utilizing BOS funds, gaining education office support, enhancing staff capacity, and developing a digital system to build an effective, sustainable library.